Pengaruh Kesejahteraan Dan Model Kepemimpinan Terhadap Produktivitas Kerja Karyawan Pada BSI KCP Cemara Asri Tahun 2020-2022 - Hasibuan, Elpina Yanti; Nasution, Yenni Samri; Inayah, Nurul (Universitas Labuhanbatu, 2024)
This study aims to examine the influence of welfare and leadership models on employee productivity at BSI KCP Cemara Asri either partially or simultaneously.This study uses quantitative methods with data collection using likert scale method. The subjects used in this study were employees of BSI KCP Cemara Asri in 2020 – 2022, which amounted to 33 respondents and were taken using sampling techniques. Data analysis techniques through IBM Spssstatistical program 26. The results of this study showed that: first, Welfare has a positive and significant effect on employee productivity with a significance value of 0.042 < 0.05. Second, the leadership Model has a positive and significant effect on employee productivity with a significance value of 0.031 < 0.05.Third, Welfare and leadership models have a positive and significant effect on employee productivity with a signicant value of 0.028 < 0.05.